KEBIJAKAN ADAPTASI PERUBAHAN IKLIM DALAM MENINGKATAN KETAHANAN PANGAN DAN GIZI BERBASIS SUSTAINABLE LIVEHOOD DI INDONESIA - Defriani Dwiyanti; Aldri Frinaldi; Rembrandt Rembrandt; Dasman Lanin; Genius Umar (Universitas Fort De Kock, 2023)
Indonesia is vulnerable to various hydrometeorological disasters, such as floods, droughts, cyclones, erosion, as well as forest and land fires. Low welfare and human resources in the agricultural and fisheries sectors due to the threat of climate change, causing a decline in production. This will lead to a decrease in the level of social welfare. Adaptation efforts to climate change are important to reduce the risk of food insecurity and malnutrition. One of the right concepts to overcome the existing problems is a sustainable livelihood approach. So this study aims to describe climate change adaptation through a sustainable livelihood approach to reduce the risk of food insecurity and malnutrition in terms of meeting the needs for social, physical, human and financial capital. This article is a literature study by collecting a number of data and theories from books, magazines, reports and journals related to the problem and research objectives. The study concludes that adaptation to climate change with a sustainable livelihood approach can increase food security and family nutrition, through social capital, natural capital, human capital, financial capital. The government can consider implementing sustainable livelihood policies carried out by local governments and related stakeholders in improving the welfare of agricultural communities